2013
DOI: 10.1111/mec.12289
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic and phenotypic responses to desiccation in natural populations of a desert drosophilid

Abstract: We used whole transcriptome microarrays to assess changes in gene expression and monitored mortality rates and epicuticular hydrocarbons (CHCs) in response to desiccation stress in four natural populations of Drosophila mojavensis from Baja California and mainland Mexico. Desiccation had the greatest effect on gene expression, followed by biogeographical variation at regional and population levels. Genes involved in environmental sensing and cuticular structure were up-regulated in dry conditions, while genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 79 publications
8
67
0
Order By: Relevance
“…S1C) and returned to basal levels within 4 h of recovery. To determine if cold-and desiccation-induced capa up-regulation also occurred in Drosophila species originating from different environments, as well as in other dipteran species, cold-and/or desiccation-induced capa mRNA changes were assessed in Drosophila montana, a coldtolerant species (28), Drosophila mojavensis, a desert-dwelling species adapted to harsh conditions including desiccation and high temperature (18,29), and two warm-acclimatized mosquito species, Aedes aegypti and Anopheles gambiae (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1C) and returned to basal levels within 4 h of recovery. To determine if cold-and desiccation-induced capa up-regulation also occurred in Drosophila species originating from different environments, as well as in other dipteran species, cold-and/or desiccation-induced capa mRNA changes were assessed in Drosophila montana, a coldtolerant species (28), Drosophila mojavensis, a desert-dwelling species adapted to harsh conditions including desiccation and high temperature (18,29), and two warm-acclimatized mosquito species, Aedes aegypti and Anopheles gambiae (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Desiccation in drosophilids also is accompanied by changes in the expression of genes associated with environmental sensing and cuticular structure (18), and one study has shown that selection for desiccation-tolerance is linked to polymorphisms in Malpighian tubule ion transport genes (19). The latter observation thus implicates tubule function in abiotic stress tolerance, providing a physiological link between desiccation and cold tolerance via ion-and water-transport mechanisms.…”
mentioning
confidence: 96%
“…Dehydration can lead to changes in the regulation of transcription/translation (Rajpurohit et al, 2013;Wang et al, 2011), with some insects showing a general decrease in protein synthesis through a down-regulation of transcription-related genes (Rajpurohit et al, 2013). However, dehydrated D. variabilis showed an up-regulation of pathways associated with transcription and translation initiation (Table 2; Table S4).…”
Section: Dehydration-induced Changes To the Transcriptomementioning
confidence: 99%
“…Several morphological and pigmentation differences have been identified across all four host races, most notably divergence in features of the male genitalia such as the shape of the aedeagus (Richmond et al 2012;Pfeiler et al 2009). Overall, D. mojavensis is highly resistant to water stress relative to other Drosophila (Gibbs et al 2003;Gibbs and Matzkin 2001;, but yet significant differences in desiccation resistance exist between Catalina, Baja California and Sonora populations (Rajpurohit et al 2013;Matzkin et al 2007). Furthermore, interpopulation differences extend to the composition of the hydrocarbons in the fly cuticle.…”
Section: Genetic Variation and Population Geneticsmentioning
confidence: 95%
“…Together these 12 species encompassed a wide breadth of the genus, with nine members of the Sophophora subgenus, and three from the Drosophila subgenus, including D. mojavensis. Although a cDNA microarray was developed for D. mojavensis prior to the genome sequencing (Matzkin et al 2006), knowledge of the genome allowed the construction of complete transcriptome oligonucleotide microarrays (Bono et al 2011;Matzkin 2012;Markow 2009, 2013;Rajpurohit et al 2013;Smith et al 2013). Additional tools for D. mojavensis include a BAC library and the availability of transgenic stocks (Song et al 2011;Holtzman et al 2010).…”
Section: Drosophila Mojavensis In the Genomic Eramentioning
confidence: 99%